Regulation of platelet activation and thrombus formation in acute non‐ST segment elevation myocardial infarction: Role of Beclin1 - Lingkun Ma; Wenjing Sun; Jingchao Li; Hailan Wang; Zihan Ding; Qing He; Yue Kang; Shujuan Dong; Yingjie Chu (Wiley, 2024)
Abstract This study aims to investigate the mechanism of platelet activation‐induced thrombosis in patients with acute non‐ST segment elevation myocardial infarction (NSTEMI) by detecting the expression of autophagy‐associated proteins in platelets of patients with NSTEMI. A prospective study was conducted on 121 patients with NSTEMI who underwent emergency coronary angiography and optical coherence tomography. The participants were divided into two groups: the ST segment un‐offset group (n = 64) and the ST segment depression group (n = 57). We selected a control group of 60 patients without AMI during the same period. The levels of autophagy‐associated proteins and the expression of autophagy‐associated proteins in platelets were measured using immunofluorescence staining and Western blot. In NSTEMI, the prevalence of red thrombus was higher in the ST segment un‐offset myocardial infarction (STUMI) group, whereas white thrombus was more common in the ST segment depression myocardial infarction (STDMI) group. Furthermore, the platelet aggregation rate was significantly higher in the white thrombus group compared with the red thrombus group. Compared with the control group, the autophagy‐related protein expression decreased, and the expression of αIIbβ3 increased in NSTEMI. The overexpression of Beclin1 could activate platelet autophagy and inhibit the expression of αIIbβ3. The results suggested that the increase in platelet aggregation rate in patients with NSTEMI may be potentially related to the change in autophagy. And the overexpression of Beclin1 could reduce the platelet aggregation rate by activating platelet autophagy. Our findings demonstrated that Beclin1 could be a potential therapeutic target for inhibiting platelet aggregation in NSTEMI.